Prevalence of Chronic Fatigue in Post COVID-19 Patients in Twin Cities: Chronic Fatigue in Post COVID-19 - Shahzadi, Komal; Shahid, Hamza; Malik, Mahnoor; Raza Khan, Hassan; Talha, Muhammad; Nazir, Pervisha (Pakistan Journal of Health Sciences, 2023)
COVID-19 is linked to clinically severe symptoms despite the initial infection has subsided. The acute symptoms and recovery from coronavirus disease 2019 (COVID-19) are mainly in the headlines. However, many people who have recovered deal with ongoing physical, mental, and psychological issues long beyond the acute stage. The most persistent and debilitating of these symptoms is fatigue. Objective: To determine the prevalence of chronic fatigue in post COVID-19 patients living in Twin cities (Rawalpindi and Islamabad). Methods: A descriptive cross-sectional survey was conducted and the data were collected from the population living in Islamabad and Rawalpindi using a non-probability convenient sampling technique. The study was completed within 6 months after the approval from the ethical committee. Data were collected through a self-structured questionnaire containing demographics and a fatigue severity scale was used to assess chronic fatigue. Results: There were 382 participants enrolled in total. Out of which 54.2% were females and 45.8% were males. According to the results of the fatigue severity scale 65.4% participants reported chronic fatigue. Out of the 207 female participants, 148 (71.5%) reported chronic Fatigue while 159 (28.5%) were non-fatigued. The results also showed that out of 175 males, 102 (58.3%) reported chronic fatigue and 59 (41.7%) were non-fatigued. Conclusions: The current study concluded that most of the population in the Twin cities (Rawalpindi and Islamabad) had a prevalence of chronic fatigue in post COVID-19 patients.